2022
DOI: 10.1371/journal.ppat.1010213
|View full text |Cite
|
Sign up to set email alerts
|

Acid stress signals are integrated into the σB-dependent general stress response pathway via the stressosome in the food-borne pathogen Listeria monocytogenes

Abstract: The general stress response (GSR) in Listeria monocytogenes plays a critical role in the survival of this pathogen in the host gastrointestinal tract. The GSR is regulated by the alternative sigma factor B (σB), whose role in protection against acid stress is well established. Here, we investigated the involvement of the stressosome, a sensory hub, in transducing low pH signals to induce the GSR. Mild acid shock (15 min at pH 5.0) activated σB and conferred protection against a subsequent lethal pH challenge. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 85 publications
(189 reference statements)
1
37
0
Order By: Relevance
“…The D L falls in the range of characterized DNA/RNA-binding proteins 45,46 , ribosomes and ribosome-binding proteins 36,37,40,47 , which suggests that the diffusion coefficient reflects the mobility of RsbR1 present in supramolecular complexes with RsbS (and probably RsbT) (RsbR1-RsbS-RsbT); the full stressosome complex has a molecular mass (1.8 MDa) comparable to that of ribosomes 22 . We also determined the mobility of RsbR1 under mild acid stress conditions (pH 5.0) as the protein has been reported to be involved in acid stress sensing in L. monocytogenes 35 . Mild acid stress triggers enhanced expression of listerial virulence genes expression and invasiveness in epithelial cells 48,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The D L falls in the range of characterized DNA/RNA-binding proteins 45,46 , ribosomes and ribosome-binding proteins 36,37,40,47 , which suggests that the diffusion coefficient reflects the mobility of RsbR1 present in supramolecular complexes with RsbS (and probably RsbT) (RsbR1-RsbS-RsbT); the full stressosome complex has a molecular mass (1.8 MDa) comparable to that of ribosomes 22 . We also determined the mobility of RsbR1 under mild acid stress conditions (pH 5.0) as the protein has been reported to be involved in acid stress sensing in L. monocytogenes 35 . Mild acid stress triggers enhanced expression of listerial virulence genes expression and invasiveness in epithelial cells 48,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Since RsbR1 senses acid stress independently of the presence of paralogous RsbRs 35 , we tested whether or not the diffusion of RsbR1 was affected by subjecting cells to a mild acidic condition at pH 5.0 (Fig. 3f).…”
Section: Rsbr1 Interacts With the Plasma Membrane In L Monocytogenes ...mentioning
confidence: 99%
“…The foodborne pathogen Listeria monocytogenes , the aetiological agent of listeriosis, is a robust bacterium capable of surviving in harsh environments including the extremely low pH of the human stomach [ 1, 2 ]. L. monocytogenes senses acidification of the environment through a multi-protein complex designated as the stressosome, composed of putative sensory proteins RsbR1 and its four paralogues, the scaffold protein RsbS and the serine–threonine kinase RsbT, which is responsible for the phosphorylation of RsbR1 and RsbS [ 3, 4 ]. Under stressful conditions, the stressosome activates a signal cascade that ultimately releases the alternative sigma factor B (σ B ) from an anti-sigma factor, culminating in the upregulation of approximately 300 genes that comprise the general stress response (GSR) regulon.…”
Section: Introductionmentioning
confidence: 99%
“…σ B probably contributes to this response since it is activated at the same low pH values that trigger the ATR, although some researchers have suggested that it is not the main regulator controlling the response [ 16 ]. In a recent study, we demonstrated the pivotal role of the stressosome in the sensing of low pH and the subsequent activation of σ B [ 3 ]. Pre-treating mid-log phase cultures at pH 5 for 15 min increased the transcription of highly σ B -dependent genes lmo2230 and lmo0596 , and enhanced L. monocytogenes acid tolerance in a stressosome-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation